2017
DOI: 10.1098/rspb.2016.2445
|View full text |Cite
|
Sign up to set email alerts
|

Natal dispersers pay a lifetime cost to increased reproductive effort in a wild bird population

Abstract: Natal dispersal is assumed to be costly. Such costs can be difficult to detect, and fitness consequences of dispersal are therefore poorly known. Because of lower phenotypic quality and/or familiarity with the environment, natal dispersers may be less buffered against a sudden increase in reproductive effort. Consequently, reproductive costs associated with natal dispersal may mostly be detected in harsh breeding conditions. We tested this prediction by comparing lifetime reproductive success between natal dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 45 publications
1
13
1
Order By: Relevance
“…Our results are not consistent with earlier studies (Gienapp & Meril€ a 2011;Waser et al 2013;Germain et al 2017) where dispersers did not incur fitness costs after recruitment. In the one earlier mammalian study (Waser et al 2013), they did not detect long-term fitness benefits for either sex likely because kangaroo rats do not show sex-biased dispersal.…”
Section: Intergenerational Effects Of Immigrationcontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results are not consistent with earlier studies (Gienapp & Meril€ a 2011;Waser et al 2013;Germain et al 2017) where dispersers did not incur fitness costs after recruitment. In the one earlier mammalian study (Waser et al 2013), they did not detect long-term fitness benefits for either sex likely because kangaroo rats do not show sex-biased dispersal.…”
Section: Intergenerational Effects Of Immigrationcontrasting
confidence: 99%
“…Because dispersal theory does not hypothesise dispersal costs and benefits to be intergenerational, we do not expect there to be intergenerational effects. Earlier studies (Waser et al ; Germain et al ) reported results consistent with immigrants making the best of a bad lot, but found no sex differences.…”
Section: Introductionmentioning
confidence: 89%
“…Immigrants had generally lower fitness than residents. This is in line with the results from a previous study on fish (Peterson et al, 2014) and some studies of birds (Verhulst and Van Eck, 1996;Bensch et al, 1998) and mammals (Martinig et al, 2020), but is not consistent with others (birds: Gienapp and Meril€ a, 2011;Germain et al, 2017;mammals: Waser et al, 2013). In another long-lived species, the Audouin's gull Larus audouinii, Oro et al (2011) compared fitness components among residents and immigrants and found differences in recapture probabilities, suggesting higher site-tenacity for residents than for immigrants, but similar survival and recruitment.…”
Section: Discussionsupporting
confidence: 80%
“…Behavioural responses to novel environments (such as exploratory behaviour and neophobia) are considered critical targets of selective pressures [ 1 3 ]. While animals exposed to unfamiliar environments generally perceive them as less predictable and more dangerous than familiar places and situations [ 4 6 ], they are often forced to explore, disperse and colonise new areas [ 7 , 8 ]. However, exploratory traits are often investigated using animals in an individual context, while the presence of conspecifics can modulate the expression of behavioural responses, for example through social facilitation (change of rate of certain behavioural responses, sensu [ 9 ]).…”
Section: Introductionmentioning
confidence: 99%